Age Differentials in Perception of Family Stress by Women - Dimkpa, Daisy I (Richtmann Publishing, 2011)
This study investigated age differentials in the perception of women towards family stress. The descriptive survey design was used and a total of 200 women were randomly selected from two public and private secondary schools and the Ministry of Education in Port Harcourt Municipal Area in Rivers State of Nigeria. The research instrument used was a researcher- designed ‘Family Stress Questionnaire’. Simple percentage and ANOVA inferential statistics were used in data analysis. The study revealed that there was a statistical significant difference among women of various age groups in their perception of family stress (F-cal. = 17.03; p<.05).Specifically, Duncan’s Multiple Range test showed that the women in the age range of 51-60yrs and 61 years and above were significantly different in their perception of family stress from those in the age range of 25-30years; 31-40 years and 41-50 years. Based on these findings, it was recommended among others that the younger women be counselled on issues relating to family stress before marriage, by employing pre-marital counselling. Using group and individual counselling techniques, counsellors should assist women generally in being assertive and to imbibe right attitudes that will help them cope with stress in the family. Keywords: Family stress, coping, age differentials, women, survey, counselling